The World Bank’s Involvement in Global and Regional Partnership Programs : An Independent Assessment - Independent Evaluation Group (World Bank, Washington, DC, 2018)
The objectives of the Global and Regional Partnership Programs (GRPPs) that Independent Evaluation Group (IEG) has reviewed have been highly relevant. Most programs have had positive achievements in terms of outputs. The sustainability of a number of programs is threatened by weak resource mobilization strategies, failure to keep up with the changing global and regional context, and difficulties in demonstrating results at the outcome level. The Bank’s management and oversight of GRPPs shows strengths and weaknesses. Many task teams have brought extraordinary dedication and ownership to their programs. The Bank hasplayed to its comparative advantage in convening and mobilizing resources for new programs.But the implementation of the Bank’s strategic and policy agenda to promote effective partnershipshas essentially stalled over the last three years.The DGF has had a number of successes, but it is no longer the umbrella facility for the Bank’sgrant financing arrangements. During its strategic reorientation toward a “venture capital” model,the DGF should focus on building sustainable institutional arrangements for new programs that can survive the Bank’s financial exit and on securing multi donor financing from the outset.